World Bank Research Digest, Vol. 1(4) - World Bank (Washington, DC, 2014)
In this issue: the urbanization of global poverty; focus: macroeconomic volatility and development; brain waste? Educated immigrants in the U.S. labor market; inefficient lobbying, populism, and oligarchy; weaponomics: the global market for assault rifles; exit and exclusion as routes to informality; and will markets direct investments under the Kyoto Protocol?